2018
DOI: 10.1002/smll.201802886
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Tumor Homing by Chemotherapy‐Loaded Nanoparticles

Abstract: Targeted delivery of anticancer drugs with nanocarriers can reduce side effects and ameliorate therapeutic efficacy. However, poorly perfused and dysfunctional tumor vessels limit the transport of the payload into solid tumors. The use of tumor‐penetrating nanocarriers might enhance tumor uptake and antitumor effects. A peptide containing a tissue‐penetrating (TP) consensus motif, capable of recognizing neuropilin‐1, is here fused to a neuroblastoma‐targeting peptide (pep) previously developed. Neuroblastoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…To this end, we used the same orthotopic model of NB planned for therapeutic studies, obtained by implantation of IMR‐32 cell line into the adrenal gland of athymic mice. [ 46,47 ] No weight loss, splenomegaly or skin rash were evidenced in all treatment groups, as well as no acute or chronic liver and kidney toxicities emerged by the quantification of AST, ALT, CRE, BUN levels in mice plasma ( Figure A,B).To rule out that the TL[miR] treatments may have an immune‐stimulatory activity, we quantified levels of 14 proinflammatory cytokines performed 6 h after the first treatment (acute immune activation, Figure 3C) and 24 h after the last treatment (late immune response, Figure 3D). This analysis confirmed that our TL[miR] did not increase cytokine levels, even when administered at the maximum dose (combo = 20 µg + 20 µg miR‐mimics per mouse).…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we used the same orthotopic model of NB planned for therapeutic studies, obtained by implantation of IMR‐32 cell line into the adrenal gland of athymic mice. [ 46,47 ] No weight loss, splenomegaly or skin rash were evidenced in all treatment groups, as well as no acute or chronic liver and kidney toxicities emerged by the quantification of AST, ALT, CRE, BUN levels in mice plasma ( Figure A,B).To rule out that the TL[miR] treatments may have an immune‐stimulatory activity, we quantified levels of 14 proinflammatory cytokines performed 6 h after the first treatment (acute immune activation, Figure 3C) and 24 h after the last treatment (late immune response, Figure 3D). This analysis confirmed that our TL[miR] did not increase cytokine levels, even when administered at the maximum dose (combo = 20 µg + 20 µg miR‐mimics per mouse).…”
Section: Resultsmentioning
confidence: 99%
“…Human (IMR-32, HTLA-230, SH-SY5Y and SK-N-AS) and murine (NXS2) neuroblastoma (NB) cell lines were grown in complete Dulbecco’s Modified Eagle Medium (DMEM) medium, as previously described [ 12 15 ]. In some experiments, IMR-32 cells were infected with retrovirus expressing the firefly luciferase (luc) gene, as previously reported [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…A recent study has shown that the resulting peptide (CRALKYSHSHSYWLRSGGG) is indeed an excellent bifunctional ligand for targeting of NB cells. This peptide when coupled to doxorubicin‐loaded liposomes increased tumor uptake, penetration, and diffusion of the payload in tumor tissues (see Figure ) and improved the antitumor effects in three xenografts of human NB …”
Section: How To Enhance Liposomal Drug Delivery and Penetration In Tumentioning
confidence: 99%
“…In particular, the therapeutic properties of DXR nanoformulations tagged with ligands capable of recognizing aminopeptidase N (APN) or A (APA) or other receptors expressed by the tumor endothelium and pericytes, or capable of targeting GD 2 expressed by NB cells, either alone or in combination, will be reviewed and discussed. Finally, we will review recent data regarding the identification and development of new tumor‐homing and tumor‐penetrating peptides (discovered by screening peptide‐phage libraries on NB mouse xenografts and patient specimens and, in some cases, fused with a motif capable of recognizing neuropilin‐1 (NRP‐1)), as well as their capability to increase liposomal drug delivery and penetration into NB tissues …”
Section: Introductionmentioning
confidence: 99%